OPEN SPACES IN MEDIUM-SIZED CITIES IN BUENOS AIRES PROVINCE: CHALLENGES AND OPPORTUNITIES FOR BLUE GREEN INFRASTRUCTURE. THE CASE OF CHASCOMÚS, ARGENTINA - Giusti, Mariana; Prados, Maria José (Cuadernos de Turismo, 2025)
The article analyzes the strategic role of public open spaces in the urban sustainability of Chascomús, a medium-sized city in the province of Buenos Aires (Argentina), under pressure from urban expansion and the consolidation of tourism as an economic activity. From an Urban Ecology and Geography perspective, and within the framework of Blue-Green Infrastructure, it evaluates their distribution, functionality, and level of consolidation. The study identifies territorial inequalities, planning deficits, and opportunities for integrating these spaces as key infrastructure within a network that links climate mitigation, social cohesion, and sustainable tourism.